Peran Aplikasi Photomath terhadap Kemampuan Pemecahan Masalah Matematika - Imaniyah, Mut; Natasya, Aulia; Putri, Ahsya Qhyla Ditya; Hernaeny, Ulfah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
The application of technology in education is growing rapidly, especially in learning mathematics. One of the widely used applications is Photomath, which assists students in solving math problems by providing solution steps. This study aims to analyze the role of Photomath application on mathematical problem-solving ability. The research method uses library research to analyze the role of Photomath application on mathematical problem-solving ability. The results showed that the use of Photomath can significantly improve mathematical problem-solving skills. However, this application also has disadvantages, such as potential student dependence on technology and reduced analytical thinking skills. This study concludes that Photomath is effective as a learning tool, but needs to be balanced with other teaching approaches to ensure deep understanding. The development of additional features that can help solve graphing problems and the improvement of the app's offline functionality are expected to support its use in learning mathematics more comprehensively.